Dynamic changes in polioviruses identified by environmental surveillance in Guangzhou, 2009–2021. Issue 3 (18th March 2023) - Chen, Meizhong; Zhang, Yong; Zhang, Wei; Huang, Shufen; Zhu, Shuangli; Li, Caixia; Guo, Xue; Zeng, Hanri; Fang, Ling; Ke, Bixia; Li, Hui; Yoshida, Hiromu; et al.
Abstract: Polio cases can be missed by acute flaccid paralysis (AFP) case surveillance alone, emphasizing the importance of environmental surveillance (ES). In this study, to investigate the serotype distribution and epidemiological trends of poliovirus (PV), we characterized PV isolated from domestic sewage in Guangzhou City, Guangdong Province, China from 2009 to 2021. A total of 624 sewage samples were collected from the Liede Sewage Treatment Plant, and the positive rates of PV and non‐polio enteroviruses were 66.67% (416/624) and 78.37% (489/624), respectively. After sewage sample treatment, each sewage sample was inoculated in six replicate tubes of three cell lines, and 3370 viruses were isolated during the 13‐year surveillance period. Among these, 1086 isolates were identified as PV, including type 1 PV (21.36%), type 2 PV (29.19%), and type 3 PV (49.48%). Based on VP1 sequences, 1057 strains were identified as Sabin‐like, 21 strains were high‐mutant vaccines, and eight strains were vaccine‐derived poliovirus (VDPV). The numbers and serotypes of PV isolates in sewage were influenced by the vaccine switch strategy. After type 2 OPV was removed from the trivalent oral PV (OPV) vaccine and a bivalent OPV (bOPV) was adopted in May 2016, the last type 2 PV strain was isolated from sewage, with no detection thereafter. Type 3 PV isolates increased significantly and became the dominant serotype. Before and after the second vaccine switch in January 2020, that is, from the first dose of IPV and second–fourth doses of bOPV to the first two doses of IPV and third–fourth doses of bOPV, there was also a statistical difference in PV positivity rates in sewage samples. Seven type 2 VDPVs and one type 3 VDPV were identified in sewage samples in 2009–2021, and phylogenetic analysis indicated that all VDPVs isolated from ES in Guangdong are newly discovered VDPVs, different from VDPV previously discovered in China, and were classified as ambiguous VDPV. It is noteworthy that no VDPV cases were reported in AFP case surveillance in the same period. In conclusion, continued PV ES in Guangzhou since April 2008 has been a useful supplement to AFP case surveillance, providing an important basis for evaluating the effectiveness of vaccine immunization strategies. ES improves early detection, prevention, and control; accordingly, this strategy can curb the circulation of VDPVs and provide a strong laboratory basis for maintaining a polio‐free status.